Okwui Enwezor Distinguished Lecture 2024 - Invisible (Hi)Story. Exploring Black East German History (Okwui Enwezor Distinguished Lecture, 2024)
The Fourth Okwui Enwezor Distinguished Lecture 2024 took place on 17 July 2024 and was held by Dr. Katharina Warda. It was entitled "Invisible (Hi)Story. Exploring Black East German History". German history is for the most part a white and West German history. The history of the GDR and East Germany after 1990 mostly appears as marginal notes. Black history is highly contested and mostly an intellectual experiment rather than anchored in German history. But what happens when the two marginalized narratives intersect? Black East German history emerges as a void, a blank space. Their individuals are doubly invisible – their stories, experiences and perspectives are virtually non-existent. Yet this doubly neglected part of German history not only contains complex histories between Blackness, socialism and internationalism. As part of East German history of color, these histories and perspectives shed a completely different light on current narratives of the Cold War and the ongoing political shift to the right. About the lecture series The Okwui Enwezor Distinguished Lecture annually features a prominent artist, curator, or scholars, individuals or collectives, who will engage with groundbreaking contributions to the rethinking of the role of arts and culture in a global perspective and celebrate the legacy of curator, historian, an poet Okwui Enwezor (1963–2019). Lecturers in 2021 and 2022 have been Prof Chika Okeke-Agulu, as well as the curatorial duo Nantume Violet and the late Ijeoma Uche-Okeke, represented by Asele Institute. Find out more about the Cluster of Excellence here: https://www.africamultiple.uni-bayreuth.de/en/index.html